Design of a model for improving emergency room performance using a colored Petri net (2024)
Emergency rooms are one of the most complex and vital areas of healthcare institutions, which have presented overcrowding, long waiting, and length of stay times, affecting the timeliness, responsiveness, and quality of service. This research aimed to design a detailed patient flow model to improve emergency room performance using the hierarchical timed colored Petri nets. Then, the model was simulated to evaluate scenarios considering tactical decisions such as physician staff planning, operational decisions such as adjusting work schedules, and strategic decisions such as increasing observation beds. The best scenario would reduce the average waiting times for triage II patients by 17.30 % and 47.57 %, and triage III by 33.49 % and 43.49 % for medical consultation in the office or the minor surgery room, respectively. In addition, the waiting time in observation and the rate of patients left without being seen by a physician would be reduced by 92.45 % and 74.67 %, respectively. These results improve the quality and timeliness of the service and avoid putting the patient's health and life at risk. The designed model included more attributes for patients concerning the place of medical care in the emergency room, the number of visits to the physician, and the physician who will care for the patient. Moreover, the simulation model includes observation beds as a limited resource blocking new patient admission. Finally, this model is a tool to support emergency room managers in making short, medium, and long-term decisions to address problems such as overcrowding, long waiting and length of stay times, and high rates of patients left without being seen by a physician